Nilai Toleransi Beragama dalam Cerpen Seribu Kunang-Kunang di Manhattan Karya Umar Kayam - Kurniatin, Titin Kurniatin; Ripaldi, Arif; Riyani, Dini (Program Studi Tadris Bahasa Indonesia, 2025)
This article analyzes the application of religious tolerance values in the short story “Seribu Kunang-Kunang di Manhattan” by Umar Kayam and its relevance to strengthening the profile of Rahmatan Lil Alamin students at Madrasah Tsanawiyah. This study makes a significant contribution to the use of literary works as a means of learning about tolerance values in formal education. It employs a qualitative approach, utilizing text analysis and literature study methods to examine the moral messages contained in the short story. The results of the analysis show that this short story effectively depicts harmonious relationships between individuals from different religious backgrounds. Values such as respect for diversity, respect for other beliefs, and the importance of interfaith cooperation are essential elements that can be implemented in the curriculum at Madrasah Tsanawiyah. Integrating these values into the curriculum encourages students to understand and respect differences while developing moderate, inclusive, and tolerant personal characters.